Neighbor danger: Yellow fever virus epizootics in urban and urban-rural transition areas of Minas Gerais state, during 2017-2018 yellow fever outbreaks in Brazil. - Lívia Sacchetto; Natalia Ingrid Oliveira Silva; Izabela Maurício de Rezende; Matheus Soares Arruda; Thais Alkifeles Costa; Érica Munhoz de Mello; Gabriela Fernanda Garcia Oliveira; Pedro Augusto Alves; Vítor Emídio de Mendonça; Rodolfo German Antonelli Vidal Stumpp; Alaine Izabela Alves Prado; Adriano Pereira Paglia; et al. (Public Library of Science (PLoS), 2020)
Background From the end of 2016 until the beginning of 2019, Brazil faced a massive sylvatic yellow fever (YF) outbreak. The 2016-2019 YF epidemics affected densely populated areas, especially the Southeast region, causing thousands of deaths of humans and non-human primates (NHP). Methodology/principal findings We conducted a molecular investigation of yellow fever virus (YFV) RNA in 781 NHP carcasses collected in the urban, urban-rural interface, and rural areas of Minas Gerais state, from January 2017 to December 2018. Samples were analyzed according to the period of sampling, NHP genera, sampling areas, and sampling areas/NHP genera to compare the proportions of YFV-positive carcasses and the estimated YFV genomic loads. YFV infection was confirmed in 38.1% of NHP carcasses (including specimens of the genera Alouatta, Callicebus, Callithrix, and Sapajus), from the urban, urban-rural interface, and rural areas. YFV RNA detection was positively associated with epidemic periods (especially from December to March) and the rural environment. Higher median viral genomic loads (one million times) were estimated in carcasses collected in rural areas compared to urban ones. Conclusions/significance The results showed the wide occurrence of YF in Minas Gerais in epidemic and non-epidemic periods. According to the sylvatic pattern of YF, a gradient of viral dissemination from rural towards urban areas was observed. A high YF positivity was observed for NHP carcasses collected in urban areas with a widespread occurrence in 67 municipalities of Minas Gerais, including large urban centers. Although there was no documented case of urban/Aedes YFV transmission to humans in Brazil during the 2016-2019 outbreaks, YFV-infected NHP in urban areas with high infestation by Aedes aegypti poses risks for YFV urban/Aedes transmission and urbanization.